Modeling the strengthening effect of Al-Cu-Fe quasicrystalline particles in Al-based metal matrix composites - Ali F.; Scudino S.; Liu G.; Srivastava V.C.; Mukhopadhyay N.K.; Samadi Khoshkhoo M.; Prashanth K.G.; Uhlenwinkel V.; Calin M.; Eckert J. (My University, 2025)
In this work, a model that simultaneously considers the combined strengthening contributions of load bearing, dislocation strengthening and matrix ligament size effects, which has been found to accurately describe the mechanical behavior of Al-based composites reinforced with complex intermetallic particles (Scudino et al. (2009) [8]), has been used to predict the mechanical properties of Al-based metal matrix composites containing different amounts of Al 62.5Cu 25Fe 12.5 quasicrystalline reinforcing particles. The present results further demonstrate the validity of this model and confirm the importance of the characteristic matrix ligament size for explaining the strengthening effect of the composites containing large volume fractions of reinforcement. © 2011 Elsevier B.V. All rights reserved.